Indonesian Coffee at The International Market - Apriani, Deassy; Marissa, Feny; Mahdi Igamo, Alghifari (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
The research was conducted to know the competitiveness of coffee in the international market both comparatively and competitively. Measuring the strength of competitiveness in this study was conducted based on comparative analysis (analysis of RCA index, Herfindahl and CR4 Index, and Trade Specialization Index / ISP) and to analyze the competitive advantage of Indonesian coffee (Berlin Porter'/ Porter's Diamond Theory theory) to see the demand and supply side of the market. The results of this study revealed that the competitiveness of Indonesian coffee is very strong supported by the average RCA value of 4.08, the Herfindahl Index which shows free competition and reveals that the market ratio includes low market concentration and Indonesia based on the Market Specialization Index including exporting countries.